PENGARUH PENGEMBANGAN PRODUK TERHADAP KEPUASAN PELANGGAN UMKM AYAM GEPREK JODER KA DHANI - Kartika Laily Panyuluh Pinasthika; Rheka Puspita; Sabrina Nihlah Nuria (Cahaya Ilmu Bangsa, 2024)
A business will not grow if customer satisfaction is not met properly. For this reason, business owners must pay attention to factors that boost customer satisfaction, such as product development. This study aims to analyze whether or not there is an effect of product development on customer satisfaction of UMKM Ayam Geprek Joder Ka Dhani. The research method used is quantitative survey with simple linear regression analysis technique. The results of the study prove that product development has a significant influence on customer satisfaction of UMKM Ayam Geprek Joder Ka Dhani. This is reinforced by evidence of calculations through the help of the SPSS version 25.00 application.